La crisis social de la política y la movilización política de la crisis: el 15-M - Benjamín Tejerina; Ignacia Perugorría (Mélanges de la Casa de Velázquez, 2017)
This article sets out to rethink the relation between mobilisation and democratisation processes in Spain since the inception of the 15M movement. More specifically, we propose to analyse: 1) the origin of the movement, sparked by the social consequences of the economic crisis and the erosion of the democratic system; 2) the 15M’s discourse and internal debate around the perceived deficiencies of politics and representative institutions; and 3) the triple process of democratisation driven by the 15M movement. With regard to this latter point, we will be examining: a) the materialisation of horizontal, deliberative and face-to-face democracy in both encampments and assemblies; b) the connective (re)mediation and the online network system put in place by the 15M; and c) the evolution from «parallel agora» to »political observatory» and, ultimately, to the re-legitimisation of (a renewed) political representation conceived as a Second Democratic Transition. Data come from the qualitative CIS study on Political Representations and 15M (2011), 20 in-depth interviews conducted by the project 15M.cc, and from manifestos and internal documents issued by new collectives and political parties born in the post-15M period.